INQUIRY TRAINING BASED E-MODULE DEVELOPMENT IN SCIENCE SUBJECTS TO IMPROVE HOTS LITERACY ABILITY OF CLASS IV SCHOOL STUDENTS BASE - John Simon Sinulingga; Retno Dwi Suyanti; Sriadhi Sriadhi (SENSEI RESEARCH CENTER, 2023)
The purpose of this study was to determine the feasibility and effectiveness of Inquiry Training-based E-Modules in science subjects to improve HOTS literacy skills for Class IV Elementary School students. This research is a type of research and development (Reasearch and Development) using the ADDIE model ( Analysis, Design, Development, Implementation, Evaluation ). The results showed that the E-Module based on Inquiry Training in science subjects to improve HOTS literacy skills was